A Common Error Analysis in Students’ English Narrative Writing - Arsen Nahum Pasaribu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This research aims to explore error analysis in students’ academic writing. The study was conducted at the University of HKBP Nommensen Medan. The method used is a mixed-method. The research participants were 26 English department students in the third semester. Thus, the research data consist of 26 narrative stories. The results showed that around 252 errors were found in all categories. The most dominant error category is omission 92 (36.51%) then is respectively followed by addition 64 (25.40%), misinformation 56 (22.22%), and disordering 40 (15.87%). The most dominant factor as the cause of the error is first language interference, and then translation and carelessness. In conclusion, all types of errors (omission, addition, misinformation, and disordering) were identified in the students’ narrative writing. Keywords: Error Analysis, Factor of Errors, Narrative Writing, University Students